2020
DOI: 10.1021/acsinfecdis.0c00369
|View full text |Cite
|
Sign up to set email alerts
|

Local and Sustained Delivery of Rifampicin from a Bioactive Ceramic Carrier Treats Bone Infection in Rat Tibia

Abstract: Next-generation treatment strategies to treat osteomyelitis with complete eradication of pathogen at the bone nidus and prevention of emergence of drug resistance is a real challenge in orthopedics. Conventional treatment strategies including long-term adherence of patients to systemic antibiotic delivery, local delivery using nondegradable vehicles, and surgical debridement are not completely effective in achieving successful results. In this study, a broad-spectrum antibiotic, rifampicin (RFP), was incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…For example, the researchers of ref. [ 56 ] designed a nanohydroxyapatite-based scaffold adopted as the drug carrier to treat bone implant-associated infection by local and sustained delivery of rifampicin. Based on in vivo and in vitro antibacterial and osteogenetic experiments, this work demonstrated that the nanohydroxyapatite-based bioceramic scaffolds, as a carrier of rifampicin, could eliminate bacterial infection while simultaneously promoting bone repair and regeneration.…”
Section: Bioceramic-based Scaffolds With Drug-induced Antibacterial F...mentioning
confidence: 99%
“…For example, the researchers of ref. [ 56 ] designed a nanohydroxyapatite-based scaffold adopted as the drug carrier to treat bone implant-associated infection by local and sustained delivery of rifampicin. Based on in vivo and in vitro antibacterial and osteogenetic experiments, this work demonstrated that the nanohydroxyapatite-based bioceramic scaffolds, as a carrier of rifampicin, could eliminate bacterial infection while simultaneously promoting bone repair and regeneration.…”
Section: Bioceramic-based Scaffolds With Drug-induced Antibacterial F...mentioning
confidence: 99%
“…Prior to incorporating antimicrobial orthopedic biomaterials in implant-associated infection in vivo models, the properties of the materials can be first evaluated in in vivo models without tibial or femoral implants (e.g., materials can be placed into dorsal subcutaneous pouches). 37,41,59,83,87,135,144,148,161 To detect the presence and concentration of eluted antibiotics from the implanted biomaterial, blood can be collected both throughout the experiment and terminally in conjunction with hard and soft tissues surrounding the material. 83,[142][143][144]161,196,197 The antibiotic can then be extracted from the serum and tissues, and high performance liquid chromatography (HPLC) and liquid chromatography− mass spectrometry (LC-MS) can be used to quantify the systemic and local concentration of the antibiotics.…”
Section: Considerations In Establishing Clinically Relevant Preclinic...mentioning
confidence: 99%
“…37,41,59,83,87,135,144,148,161 To detect the presence and concentration of eluted antibiotics from the implanted biomaterial, blood can be collected both throughout the experiment and terminally in conjunction with hard and soft tissues surrounding the material. 83,[142][143][144]161,196,197 The antibiotic can then be extracted from the serum and tissues, and high performance liquid chromatography (HPLC) and liquid chromatography− mass spectrometry (LC-MS) can be used to quantify the systemic and local concentration of the antibiotics. 83,[142][143][144]161,196,197 Following euthanasia, residual drug remaining entrapped in the implanted material can be extracted and evaluated for its concentration and antimicrobial activity in the zone of inhibition assays.…”
Section: Considerations In Establishing Clinically Relevant Preclinic...mentioning
confidence: 99%
“…In the present work, we have explored the uptake of purified exosomes by MSCs, their cell differentiation, and regenerative potential. To evaluate their regenerative potential, purified exosomes were delivered locally at a bone injury site using a biphasic (calcium sulfate–nano-hydroxyapatite) nanocement (NC), which is a biocompatible bone void filler. ,, NC + gentamicin (NCG) was functionalized with exosomes isolated either from MSCs cultured in normal (NCG + EX) or osteogenic media (NCG + OMEX) or from osteoblast (Saos-2) cells (NCG + OEX) . Effects of different exosomes types on bone formation were analyzed by micro-computer tomography (microCT) and histological analysis of bone samples 8 weeks post-implantation.…”
Section: Introductionmentioning
confidence: 99%